Childfree sebagai Tantangan Pastoral Perkawinan Katolik (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
The childfree phenomenon, the decision of married couples not to have children, is gaining increasing attention among young people, including within the Catholic Church. This choice arises in response to various modern factors, such as economic considerations, careers, personal freedom, and changing views on the meaning of family. This study aims to explore the views of young Catholics in the Semarang Vicarage on the childfree phenomenon and analyze them in light of the Catholic Church's teachings on marriage, which place procreation and education as one of the essential purposes of marriage. The study used a mixed-methods approach through the distribution of quantitative surveys and in-depth qualitative interviews. The results indicate a tension between the modern values ​​adopted by young people and the Catholic Church's teachings on openness to life. This phenomenon poses a serious pastoral challenge, particularly regarding the regeneration of the congregation and the sustainability of church life. Therefore, the Church is expected to formulate a more dialogical, contextual, and inclusive pastoral approach in accompanying young people to remain faithful to the Church's teachings without ignoring the social realities they face.